Pengaruh Persepsi Harga, Promosi dan Brand Image Terhadap Keputusan Pembelian : Studi pada Konsumen Sepatu Converse di Jakarta Barat - Tazkiyah, Umi; Vildayanti, Rina Ayu (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of price perception, promotion, and brand image on purchasing decisions for Converse shoes in West Jakarta. In the increasingly competitive fashion industry, companies are required to understand the factors that influence consumer behavior in making purchasing decisions. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 respondents who were consumers of Converse shoes in the West Jakarta area. The sampling technique used was non-probability sampling with an accidental sampling approach. The research instrument used a Likert scale to measure respondents' perceptions of price perception, promotion, brand image, and purchasing decisions. The collected data were analyzed using SPSS version 26 through descriptive statistical analysis and hypothesis testing. The results indicate that price perception, promotion, and brand image have a significant influence on purchasing decisions for Converse shoes in West Jakarta, both partially and simultaneously. These findings suggest that appropriate price perceptions, effective promotional strategies, and a strong brand image can increase consumer interest and purchasing decisions. Therefore, companies should strategically consider these factors in designing marketing strategies to enhance competitiveness and strengthen consumer loyalty.